Pengembangan Aplikasi Android Rekomendasi Gym di Kota Malang dengan Group Decision Support System dan Location Based Service - Muhammad Aufa Athallah; Ratih Kartika Dewi; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Gym, also known as a gymnasium, is a closed location for people who want to maintain fitness. The number of students and residents in Malang city is the ideal place to open a gym. However, many gym locations in the city of Malang make students and citizens confused to choose the location of the gym they want to rent. Ignasius Tri has developed an application to provide recommendations for gym locations. The application is abIe to provide gym recommendations based on weight values ​​from distance, price, and rating criteria given by the user. However, the problem is that the application is onIy abIe to accept input from one user and visiting the gym is sometimes done in groups. Development of a gym recommendation android application in Malang was developed with an Android-based Group Decision Support System and Location Based Services with TOPSIS (Technique for Order Preference by SimiIarity to ldeaI SoIution) and Borda algorithms with criteria in the form distance between the user and gym location, rental prices, and rating. Data is stored in Google firebase. Based on the tests carried out, the results from the Blackbox application test are worth 100% and the functionality is declared valid. The algorithm's viladation testing yields the same 100% value. The usability test yields a value of 79.5 indicating a Good rating for the adjective rating and a grade C grade on the percentile rank.